The Oscillograms and the physiology of audition - KH, Krishnamurthy (Journal of All India Institute of Speech and Hearing, 1972)
As the functioning of the cochlea is understood at present, the basilar membrane on the impact of sound waves registers distinctly recognisable movements. The latters’ final mechanical effect however is the shearing action of the hairs of cort against the superjascent tectorial membrane (Davis, 1958; Zalin, 1961). Subsequent to this, cytochemical (Vinnikov and Titova, 1963 and 1964) and electrical (Wever, 1966) changes take over. The mechanical reactions of the basilar membrane thus form a crucial step in audition. It is also recognised that among the various cochlear structures it is this membrane that possesses the necessary extent, physical property and histology (Engstrora, 1955) to effectively intervene within the cochlear fluids the passage of sound viz. the micropressure changes caused by it in the medium and be responsible for handing it over further to the hair cells (Wever and Lawrence, 1954). However, the observable mechanical as well as electrical responses of the membrane to the stimulus is known since long (Lawrence, 1966) to be considerably broad while the actual auditory response is quite sharp. For instance, a great discrepancy is noticeable in the resolution of pitch. Our descrimination of pitches is fixer than what is indicated by the known responses of the membrane. For example, a trained ear can discern a change of even 2-3 frequency range in an incoming sound while the membrane’s known responses are never so fine.